2010
DOI: 10.5137/1019-5149.jtn.3838-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the foramen magnum, occipital condyle and jugular tubercle

Abstract: The OC and JT are the main bony prominences obstructing the anterolateral surface of the brainstem. Neurosurgeons should be familiar with variations of the structures surrounding the FM in order to perform the safest and widest exposure possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
0
42
1
3
Order By: Relevance
“…A larger distance provides a free corridor for posterolateral approaches [3] and a longer corridor provides a wider space for a far lateral transcondylar approach [31]. In our study, the distance between OC posterior tip and opisthion was 27,52±2,59mm, the distance between OC anterior tip and opisthion 39,43±3,34 mm, and the distance between OC anterior tip and basion 12,09±1,76 mm.…”
Section: Far Lateral Approachmentioning
confidence: 72%
See 3 more Smart Citations
“…A larger distance provides a free corridor for posterolateral approaches [3] and a longer corridor provides a wider space for a far lateral transcondylar approach [31]. In our study, the distance between OC posterior tip and opisthion was 27,52±2,59mm, the distance between OC anterior tip and opisthion 39,43±3,34 mm, and the distance between OC anterior tip and basion 12,09±1,76 mm.…”
Section: Far Lateral Approachmentioning
confidence: 72%
“…Also, a long OC may require a more extensive resection for optimum visualization. Similar surgical considerations may be correct for the OC width [31]. Surgery in a wider condyle may be more demanding [12].…”
Section: Far Lateral Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our data was somehow nearer to Turkey's cases. Where, it was been reported that length of OC (Occipital condyle) 23.7±2.6, width of OC 9±14.5, Occipital condyle anterior border-Basion 9.9±1.9 and Occipital condyle posterior border--Opisthion 26.6±1.8, respectively (Avci et al, 2011). Muthukumar et al, showed that the distance of the posterior border of the OC from opisthion is important because a longer corridor provides a wider space for a far lateral transcondylar approach.…”
Section: Discussionmentioning
confidence: 99%